A mathematical description of the separation of gas mixtures generated by the thermal utilization of waste - Вамболь, Сергей Александрович; Шахов, Юрий Васильевич; Вамболь, Виола Владиславовна; Петухов, Илья Иванович (Eastern-European Journal of Enterprise Technologies, 2016)
The study focuses on the problems of the mathematical description of separating the flows of gas mixtures in the technological process of an environmentally-friendly utilization of waste. The devised mathematical calculation models use the conventional ratios of thermodynamics and the heat-and-mass exchange, including the Peng-Robinson equation of state (PR EOS) for describing the coefficients of thermal and physical properties of the working media. These models represent systems of equations that allow determining the temperatures of the coolant and the cooling air at the outlet of the heat exchanger with predetermined ratios of the mass of coolant and the air flow. In addition, the suggested equation systems allow determining the component composition of the product that is a part of the rectifying column and its output final products. The calculation shows that the rectifying column generates two flows of a gas mixture. The first flow is a gas mixture with a methane content of 89.2% and, therefore, is a valuable motor fuel for vehicles or a fuel for household purpose. The second flow of the gas mixture, given its high hydrogen content (about 34.0%), may be used as a source of energy for maintaining the gasification of waste during its utilization. The preparation of such energy sources makes the waste utilization process cost-effective. Establishing links between the functional elements that are used in a power technology plant allows devising a system of equations for the entire plant. The subject of further research is the mathematical description of the entire system and the selection of an acceptable option of the PTP arrangement that would facilitate its practical implementation.